The Analyzing The Formulation of Education Policy: Legislative Work Programs in The Education Sector - Hasanah, Mizanul; Sain, Zohaib Hassan; Ummah, Rofiatul; Ma’arif, Syamsul (Journal of Education and Learning Innovation, 2026)
The main challenge in regional education development lies in the suboptimal formulation of policies produced by legislative members, which often fail to fully address the needs of communities and educational institutions. This study examines the work programs of legislative members in the education sector in Gresik, with the hypothesis that there is a gap between policy formulation and its actual implementation in the field. The research subjects included legislative members responsible for education and relevant stakeholders, employing a qualitative methodology through in-depth interviews, policy document analysis, and observation of the legislative process. The findings reveal that the formulation of education policies in Gresik remains heavily influenced by political interests, lacks sufficient public participation, and is not fully based on the actual needs of educational institutions. The discussion emphasizes the necessity of strengthening community participation mechanisms, enhancing data-driven planning, and ensuring transparency within the legislative process to produce education policies that are more relevant, equitable, and effective. Thus, this study contributes to the literature on public policy and provides practical recommendations for improving the quality of education governance at the regional level.